1998
DOI: 10.1093/ageing/27.4.443
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic liver abscesses: a comparison of older and younger patients

Abstract: Elderly patients with pyogenic liver abscess have some subtle differences in clinical and laboratory presentation, but these do not appear to delay diagnosis. Active management is tolerated well, with no difference in mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 19 publications
4
22
5
Order By: Relevance
“…Moreover, this study revealed that presenting RUQ tenderness in older patients occurred less frequently than in the young despite the higher frequency of biliary aetiology/ disorders in older patients. However, our data did not support the postulation by Smoker et al [8], as this subtle feature in older patients may contribute to a delay in PLA diagnosis. The mean duration of symptoms prior to admission was 5.3 days and the mean time until diagnosis of PLA was made after admission was 1.4 days in older patients, which is shorter than the corresponding times reported in previous studies [8,12,13].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Moreover, this study revealed that presenting RUQ tenderness in older patients occurred less frequently than in the young despite the higher frequency of biliary aetiology/ disorders in older patients. However, our data did not support the postulation by Smoker et al [8], as this subtle feature in older patients may contribute to a delay in PLA diagnosis. The mean duration of symptoms prior to admission was 5.3 days and the mean time until diagnosis of PLA was made after admission was 1.4 days in older patients, which is shorter than the corresponding times reported in previous studies [8,12,13].…”
Section: Discussioncontrasting
confidence: 99%
“…First, some discrepancies in clinical features existed between the older and younger PLA patients. As described in the literature [8,12,13], older PLA patients are more likely to have a biliary abnormality/aetiology or underlying malignancy, whereas younger PLA patients are more likely to be males, to have RUQ tenderness, alcoholism and a cryptogenic aetiology. Polymicrobial or anaerobic infections with MDR organisms, a pleural effusion, inappropriate initial antibiotic selection and a greater severity of illness on admission occur more frequently in older PLA patients than younger patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…1 This parallels the increased incidence of biliary tract disease in older populations. 3,4 Risk factors for pyogenic liver abscess include male sex, advanced age, biliary tract disease, diabetes mellitus, liver transplantation, malignancy and percutaneous treatments for hepatocellular carcinoma, including radiofrequency ablation. 1,5 The most common clinical features include fever (73%), chills (45%) and right upper quadrant pain (38%).…”
Section: Discussionmentioning
confidence: 99%